(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
In the dictatorships of the Southern Cone, repression was responsible for a series of violations such as imprisonment, torture, and death. In these regimes, forced disappearance represented the ultimate annihilation of the enemy. For family and friends, especially children, what remained was dealing with the impossibility of mourning, sudden and permanent absence, and incomprehension about militancy versus repression. Thus, this text aims to analyze how parental absence through murder or forced disappearance altered the private dynamics of children. As sources, we will use the documentary “15 filhos”, the final reports of the National Truth Commission and the Truth Commission of the State of São Paulo, as well as the book “Infância roubada”.